Human development index, geographic disparities and strategies to reduce maternal mortality in Indonesia : an ecological study - Ramadhani, Ramadhani; Tri Yunis Miko Wahyono (Poltekkes Kemenkes Yogyakarta, 2024)
Recent data shows disparities and setbacks in maternal health services. In Indonesia, there was an increase in maternal mortality in 2020 compared to 2019. Inequality is a powerful predictor of maternal mortality. This study aims to find whether inequality indicators, namely the Human Development Index and Geographic Units, can be predictors of maternal mortality. This research uses an ecological study design with a unit of analysis in 34 provinces in Indonesia. The data used in this study is secondary data from the Ministry of Health and Statistics Indonesia. Descriptive analysis and Poisson regression were used to determine whether the Human Development Index and geographic units could be predictors of maternal mortality. The increase in maternal mortality occurred in 21 (61%) provinces in Indonesia. The province's lowest maternal mortality rate was 48, and the highest was 565 per 100,000 live births. The Human Development Index and geographic units can significantly predict maternal mortality (P < 0.05). Human development indices and geographic units are significant predictors of maternal mortality. Strategies that can be done to reduce maternal mortality are improved education, health services, and specific and collaborative interventions according to provincial needs.